Standar Mutu Pendidikan di MA Al Amiriyyah Blokagung Banyuwangi - Kholid Asrori; Naili Yaturrochmah (ICO EDUSHA, 2023)
To be able to measure and understand the quality of the education system more effectively, the development of a quality index based on national standards is a very useful tool. This education quality index provides a comprehensive and measurable measure of various aspects of education quality. Through this index, aspects such as curriculum, teaching staff, facilities, management and student learning outcomes can be measured and assessed objectively. This research uses qualitative methods while data collection techniques are carried out using interviews, observation and documentation. Data analysis includes data reduction, data presentation and drawing conclusions or verification. Validity checking is carried out using a triangulation system. The research informants were school principals and teaching staff. The results of the research show that the educational quality standards at MA Al-Amiriyyah. The results of this research are: (1) Content Standards and Competency Standards for Graduates at MA Al-Amiriyyah Blokagung (2) Standards for Qualifications of Educators and Teaching Personnel at MA Al-Amiriyyah Blokagung. (3) Process Standards at MA Al-Amiriyyah Blokagung(4) Management Standards at MA Al-Amiriyyah Blokagung (5) Standards for Facilities and Infrastructure at MA Al-Amiriyyah . Blokagung. (6) Financing Standards at MA Al-Amiriyyah Blokagung. (7) Financing Standards at MA Al-Amiriyyah Blokagung. Keywords: Standards, Education Quality Daftar Pustaka Arianto Dedi.2019.Manajemen Peningkatan Mutu Madrasah Aliyah Berbasis Pesanten. Disertasi Uin Malang. Arikunto Suharsimi. 2014. Prosedur Penelitian Kuantitatif, Kualitatif, Dan R&D. Bandung: Alfabeta. Arikunto Suharsimi. Cepi Safruddin Jabar.2014. Evaluasi Program Pendidikan. Jakarta: Pi Bumi Aksara. Dhofier Zamakhsyari.2011.Tradisi Pesantren Studi Tentang Pandangan Hidup Kyai. Jakarta: Lp3es. Fachrudin Yudhi.2021. Strategi Mutu Pendidikan, Jurnal Dirsah,(Online) Vol.4 No.2. Fadillah M. Kharis. 2015. Manajemen Mutu Pendidikan Islam Di Pesantren Studi Kasus Di Pondok Modern Darussalam Gontor, Jurnal Atta‟dib (Vol. 10.No.1) Haryono, Budiyono, Istyarini, Wardi, A. Ardiantoro. 2019.Sistem Penjaminan Mutu Pendidikan Dalam Meningkatkan Mutu Pendidikan Sekolah Dasar 134 Di Kecamatan Gajah Mungkur Kota Semarang, Jurnal Panjar: Pengabdian Bidang Pembelajaran. (Vol. 1, No. 1) Khoirul, W. (2015). Implementasi Standar Isi, Standar Proses, Dan Standar Kompetensi Lulusan Sebagai Standar Mutu Pendidikan Mts Negeri Di KabupatenTulungagung. Jurnal pedagogi,(online), 4(1). Michael, Saldana Johnny.2014. Qualitative Data Analysis, A Methods Sourcebook. Los Angeles: Sage. Moleong Lexy J. 2014. Metodologi Penelitian Kualitatif, Edisi Revisi. Bandung: Pt Remaja Rosdakarya. Moleong Lexy J. 2005. Metode Penelitian Kualitatif. Bandung: Pt Remaja Rosda Karya. Muhith Abd. 2017. Dasar Dasar Manajemen Mutu Terpadu Dalam Peendidikan. Yogyakarta: Samudra Biru. Sani Ridwan Abdullah, Pramuniati Isda, Mucktiany Anies. 2015. Penjaminan Mutu Sekolah. Jakarta : Bumi Aksara. Setiadi. 2015. Publikasi Ilmiah Guru, Kegiatan Professional Guru Sebagai Pengembangan Keprofesian Berkelanjutan. Yogyakarta: Deepublish. Siswopranoto, M. F. (2022). Standar Mutu Pendidikan. Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 6(1), 17-29. Soehartono Irwan. 2008. Metodologi Penelitian Sosial Suatu Teknik Bidang Kesejahteraan Dan Ilmu Sosial Lainnya Pendekatan. Bandung: Pt Remaja Rosdakarya. Sugiono. 2013. Metode Penelitian Pendidikan (Pendekatan Kualitatif, Kuantitatif, R&D). Bandung:Valfabeta. Sukmadinata Nana Syaodih. 2016. Metode Penelitian Pendidikan .Bandung:Pt Remaja Rosydakarya. Sulistya Joko. 2016. Mengakali Ujian Nasional Dengan Early Detektion Yogyakarta: Deepublish. Sutrisno. 1992. Kapita Selekta Ekonomi Indonesia. Yogyakarta: Andi Offset. Syafii, A., Bahar, B., Shobicah, S., & Muharam, A. (2023). Pengukuran Indeks Mutu Pendidikan Berbasis Standar Nasional. Jurnal Multidisiplin Indonesia, 2(7), 1697-1701. Daftar Pustaka Arianto Dedi.2019.Manajemen Peningkatan Mutu Madrasah Aliyah Berbasis Pesanten. Disertasi Uin Malang. Arikunto Suharsimi. 2014. Prosedur Penelitian Kuantitatif, Kualitatif, Dan R&D. Bandung: Alfabeta. Arikunto Suharsimi. Cepi Safruddin Jabar.2014. Evaluasi Program Pendidikan. Jakarta: Pi Bumi Aksara. Dhofier Zamakhsyari.2011.Tradisi Pesantren Studi Tentang Pandangan Hidup Kyai. Jakarta: Lp3es. Fachrudin Yudhi.2021. Strategi Mutu Pendidikan, Jurnal Dirsah,(Online) Vol.4 No.2. Fadillah M. Kharis. 2015. Manajemen Mutu Pendidikan Islam Di Pesantren Studi Kasus Di Pondok Modern Darussalam Gontor, Jurnal Atta‟dib (Vol. 10.No.1) Haryono, Budiyono, Istyarini, Wardi, A. Ardiantoro. 2019.Sistem Penjaminan Mutu Pendidikan Dalam Meningkatkan Mutu Pendidikan Sekolah Dasar 134 Di Kecamatan Gajah Mungkur Kota Semarang, Jurnal Panjar: Pengabdian Bidang Pembelajaran. (Vol. 1, No. 1) Khoirul, W. (2015). Implementasi Standar Isi, Standar Proses, Dan Standar Kompetensi Lulusan Sebagai Standar Mutu Pendidikan Mts Negeri Di KabupatenTulungagung. Jurnal pedagogi,(online), 4(1). Michael, Saldana Johnny.2014. Qualitative Data Analysis, A Methods Sourcebook. Los Angeles: Sage. Moleong Lexy J. 2014. Metodologi Penelitian Kualitatif, Edisi Revisi. Bandung: Pt Remaja Rosdakarya. Moleong Lexy J. 2005. Metode Penelitian Kualitatif. Bandung: Pt Remaja Rosda Karya. Muhith Abd. 2017. Dasar Dasar Manajemen Mutu Terpadu Dalam Peendidikan. Yogyakarta: Samudra Biru. Sani Ridwan Abdullah, Pramuniati Isda, Mucktiany Anies. 2015. Penjaminan Mutu Sekolah. Jakarta : Bumi Aksara. Setiadi. 2015. Publikasi Ilmiah Guru, Kegiatan Professional Guru Sebagai Pengembangan Keprofesian Berkelanjutan. Yogyakarta: Deepublish. Siswopranoto, M. F. (2022). Standar Mutu Pendidikan. Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 6(1), 17-29. Soehartono Irwan. 2008. Metodologi Penelitian Sosial Suatu Teknik Bidang Kesejahteraan Dan Ilmu Sosial Lainnya Pendekatan. Bandung: Pt Remaja Rosdakarya. Sugiono. 2013. Metode Penelitian Pendidikan (Pendekatan Kualitatif, Kuantitatif, R&D). Bandung:Valfabeta. Sukmadinata Nana Syaodih. 2016. Metode Penelitian Pendidikan .Bandung:Pt Remaja Rosydakarya. Sulistya Joko. 2016. Mengakali Ujian Nasional Dengan Early Detektion Yogyakarta: Deepublish. Sutrisno. 1992. Kapita Selekta Ekonomi Indonesia. Yogyakarta: Andi Offset. Syafii, A., Bahar, B., Shobicah, S., & Muharam, A. (2023). Pengukuran Indeks Mutu Pendidikan Berbasis Standar Nasional. Jurnal Multidisiplin Indonesia, 2(7), 1697-1701.